Implementing the Project-Based Learning Model to Enhance Students’ Critical Thinking Skills at SMP Negeri 29 Makassar - Norma Nasir; Mar Athul Wazithah T (Cita konsultindo, 2026)
Critical thinking skills are essential competencies in mathematics education, enabling students to analyze problems, evaluate information, and construct logical arguments. However, students’ critical thinking abilities are often underdeveloped due to the dominance of teacher-centered instructional practices. This study aims to examine the effectiveness of the Project-Based Learning (PjBL) model in enhancing students’ critical thinking skills in mathematics at SMP Negeri 29 Makassar. This research employed a quantitative approach using a quasi-experimental design with a one-group pretest–posttest model. The participants consisted of 32 students. Data were collected through a critical thinking test administered before and after the implementation of the PjBL model. The data were analyzed using descriptive statistics, normality and homogeneity tests, paired sample t-test, and N-Gain analysis. The results revealed a significant improvement in students’ critical thinking skills. The mean score increased from 62.34 in the pretest to 84.12 in the posttest. The paired sample t-test showed a statistically significant difference (p < 0.05), indicating the effectiveness of the intervention. Furthermore, the N-Gain value of 0.58 was categorized as moderate, suggesting a meaningful level of improvement. These findings indicate that the implementation of the Project-Based Learning model effectively enhances students’ critical thinking skills by promoting active engagement, collaboration, and reflective learning. Therefore, PjBL can be considered a suitable instructional approach for fostering higher-order thinking skills in mathematics education.